Analytical performance evaluation of a wireless mobile communication system with space diversity - Mowla, Mohammad Jabir; Zaman, Mohammad Shabab (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2007.